Assessing the Role of Government Spending in Education and Economic Growth in Malaysia - Othman, Norashida; Abdul Kapar, Nur Izzatul Jannah; Wahab, Siti Norida; Rizkalla, Nosica (Advances in Social Sciences Research Journal, 2024)
Education is a key driver in developing human capital, which refers to a workforce’s skills, knowledge, and abilities. A well-educated and skilled human capital resulted in being more productive, innovative, and adaptable to economic changes. This, in turn, contributes to higher economic growth. However, insufficient government spending on education poses a significant challenge, hindering human capital development essential for economic growth. Thus, the purpose of this study is to examine the role of government spending in education (TEDU) on economic growth (GDP) in Malaysia from 1990 to 2020 using Ordinary Least Square (OLS) estimation methods. Foreign Direct Investment (FDI) and total unemployment (UNEMP) are also included in the study as control variables. The result showed that TEDU and FDI are positively cointegrated with GDP, while UNEMP is negatively cointegrated with GDP. Findings show that government expenditure on education acts as a strategic investment that can extensively impact economic growth by promoting human capital development, enhancing productivity, and establishing a more inclusive and competitive economy. Policymakers should prioritize sustained investment in education for long-term economic development and global competitiveness.